In All Seriousness: Humour in Adibah Amin’s As I was Passing and As I was Passing II (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper investigates Adibah Amin’s use of humour in the two volumes of her occasional writing, As I was Passing (2007). To pursue this objective, the theory of humour formulated by John Morreall, a renowned contemporary figure in humour studies, has been used to frame the discussion. However, since Morreall focuses mostly on spoken humour, the paper also makes references to Dominic Cheetam’s work on written humour. The analysis shows that some elements fundamental to humour that can be found in Adibah Amin’s writing are the presence of cognitive shifts that involve expectations and violation thereof, the play mode that induces practical disengagement, and the sense of enjoyment that is exhilarating and liberating. Furthermore, Adibah Amin uses humour to promote intellectual and moral values. Besides making use of incongruities in things, Adibah Amin also includes some incongruities in presentation in her writing, which deal with her comical adaptations of linguistic patterns, further proving her astute use of humour.